PHYSICOCHEMICAL PROPERTIES, CHEMICAL COMPOSITION AND ANTIOXIDANT ACTIVITY OF THE ESSENTIAL OIL OF Citrus jambhiri (Rough lemon) ESSENTIAL OIL - del Carpio Jiménez, Carla (2022)
Citrus peels contain many essential oils with many applications in the pharmaceutical, cosmetic, and food industries. In recent years the citrus industry in our country has had a great boom due to the increase in domestic production and the growth trend of exports, because of the international level the eating habits of consumers have been changing and they are looking for functional foods, so citrus fruits have gained a lot of attention. One of the citrus fruits that have been attracting a lot of attention in countries such as India and Nigeria are Citrus jambhiri, which is also grown in our country and has a very interesting essentialoil in its peels. The aim of this research was to extract the oil from the peel of C. jambhiri using the steamdistillation method and to quantify by gas chromatography coupled to mass spectrometry the main components present in the essential oil, and then compare the percentage yield and the main components present in the peels of other citrus species. The main organoleptic and physicochemical properties of the oil were also established. It was possible to establish that the percentage yield of C. jambhiri oil was 0,72%. In the composition of the essential oil of the peels of C. jambhiri, monoterpene hydrocarbons stand out with 76,5%, the most abundant being limonene (37,7%), β-pinene (25,1%) and E-β- ocimene (5,6%), oxygenated monoterpenes constitute 15%, the majority being citronellal (4,9%) and linalool (4,1%) and sesquiterpene hydrocarbons (β-caryophyllene) at 2,8%. Among its physicochemical properties, a density (20°C) of 0,844 g/mL ± 0,02, a refractive index (20°C) of 1,472 ± 0,01 and a pH of 4,7 ± 0,01 were found. The IC50 determined for the essential oil of C. jambhiri was 99,8 ± 5,6 mg/mL.